The Most Promising Innovation Solutions to Encourage a Conversion of the Existing Urban Areas into Smart Cities - Vasylchenko, Mariana; Khrystenko, Olena; Rzhepishevska, Vita; But, Tetyana (International Journal of Engineering and Technology, 2018)
The given paper is dedicated to the determination of the most promising innovation solutions to encourage a rapid conversion of the urban areas into the advanced Smart Cities. The main purpose of this research is to put everyone in the picture about the nature of the Smart City concept and to analyse the state of implementing the idea of Smart Cities in the European countries in order to define the most widely used smart solutions on this area. It is proved that Smart Cities are based on the competitiveness of cities and regions, social capital, governance and new public management, including the use of advanced technologies among these core elements. The research has been developed through a critical review of literature related to Smart City development all over the world. It is also revealed that Smart Cities exist on the close intersection of digital technology, disruptive innovation and urban environments. Consequently, a city can be defined as a â€œsmartâ€ one, when investments in human and social capital, infrastructure projects and disruptive technologies fuel sustainable economic growth and a high quality of life, with an effective management of the available natural resources, through participatory governance.Â Â Â